Efficiency and Droop Improvement in GaN-Based High-Voltage Flip Chip LEDs - Yen-Chih Chiang; Bing-Cheng Lin; Kuo-Ju Chen; Sheng-Huan Chiu; Chien-Chung Lin; Po-Tsung Lee; Min-Hsiung Shih; Hao-Chung Kuo (International Journal of Photoenergy)
The GaN-based high-voltage flip chip light-emitting diode (HVFC-LED) is designed and developed for the purpose of efficiency enhancement. In our design, the distributed Bragg reflector (DBR) is deposited at the bonded substrate to increase the light extraction. After the flip chip process, the general current-voltage characteristics between the flip chip sample and the traditional sample are essentially the same. With the help of great thermal conductive silicon substrate and the bottom DBR, the HVFC-LED is able to enhance the power by 37.1% when compared to the traditional high-voltage LEDs. The wall-plug efficiencies of the HVFC-LED also show good droop reduction as high as 9.9% compared to the traditional devices.